Một số giải pháp giáo dục ý thức chính trị cho sinh viên hiện nay - Lê , Thị Ánh Vân (Tạp chí Giáo dục, 2023)
Today, in the context of globalization that brings a lot of opportunities and challenges, the political consciousness of young people before the period of innovation needs attention. Specially, students are high human resources, the country’s future owners, they should be educated and refresher of traditional values, revolutionary ideals clearly. The article presents the necessity of political consciousness education for students and proposes some solutions to contribute to the education of political consciousness for Vietnamese students today. Thereby, it is expected to contribute to improving the quality and effectiveness of political consciousness education for students - one of the tasks of higher education, towards the common goal of building the future generation “to be both socialist-minded and vocationally proficient”, meeting the requirements of the cause of national construction and defense.